2008
DOI: 10.1007/s10802-008-9232-x
|View full text |Cite
|
Sign up to set email alerts
|

Do Theory of Mind and Executive Function Deficits Underlie the Adverse Outcomes Associated with Profound Early Deprivation?: Findings from the English and Romanian Adoptees Study

Abstract: Theory of Mind (ToM) and Executive Function (EF) have been associated with autism and with attention-deficit hyperactivity disorder (ADHD), and hence might play a role in similar syndromes found following profound early institutional deprivation. In order to examine this possibility the current study included a group of 165 Romanian adoptees, of whom 144 were adopted into the UK from deprived institutional settings before 43months of age, and a group of 52 within-UK adoptees, all adopted before 6months of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
188
5
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(219 citation statements)
references
References 55 publications
17
188
5
9
Order By: Relevance
“…Although the decreased D2 receptor binding (CC genotype) has been associated with poorer performance on timed attention tests in previous studies (Slagter et al., 2012; Yang et al., 2004), the main effect of genotype in our study emerged in two‐way ANCOVA with childhood trauma category as another fixed factor, showing that CC homozygotes who have experienced childhood trauma perform more poorly on a sustained attention test, compared to those who have not experienced childhood adversity. The effect of early life stress on cognitive outcomes has been repeatedly demonstrated in earlier studies (Bos et al., 2009; Colvert et al., 2008), and it is to be expected due to the long maturation period of the PFC (Gogtay & Thompson, 2010; Gogtay et al., 2004) and high concentration of glucocorticoid receptors and dopaminergic projections in the PFC (Pani et al., 2000). However, it should be noted that the genotype–early life stress interaction was only found in the RVP test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the decreased D2 receptor binding (CC genotype) has been associated with poorer performance on timed attention tests in previous studies (Slagter et al., 2012; Yang et al., 2004), the main effect of genotype in our study emerged in two‐way ANCOVA with childhood trauma category as another fixed factor, showing that CC homozygotes who have experienced childhood trauma perform more poorly on a sustained attention test, compared to those who have not experienced childhood adversity. The effect of early life stress on cognitive outcomes has been repeatedly demonstrated in earlier studies (Bos et al., 2009; Colvert et al., 2008), and it is to be expected due to the long maturation period of the PFC (Gogtay & Thompson, 2010; Gogtay et al., 2004) and high concentration of glucocorticoid receptors and dopaminergic projections in the PFC (Pani et al., 2000). However, it should be noted that the genotype–early life stress interaction was only found in the RVP test.…”
Section: Discussionmentioning
confidence: 99%
“…This susceptibility may be due to its high density of glucocorticoid receptors and dopaminergic projections (Pani, Porcella, & Gessa, 2000), and the fact that it is one of the last brain regions to reach maturity (Gogtay & Thompson, 2010; Gogtay et al., 2004). In support of this, deficits in functions mediated by PFC and cortico‐striatal networks, such as attention, working memory and other executive functions, have also been reported in individuals who have experienced childhood trauma (Bos, Fox, Zeanah, & Nelson, 2009; Colvert et al., 2008). …”
Section: Introductionmentioning
confidence: 99%
“…EF has been thought of as comprising three overlapping component skills: cognitive flexibility/rule shifting, updating/working memory, and inhibitory control (30). Previous laboratory studies with older PI children have shown reduced performance on each of these components: cognitive flexibility (11), working memory performance (11,12,15), and inhibitory control (13,15,31). Additionally, there are extensive reports that PI children show attention deficits and hyperactivity symptoms that persist into adolescence (32,33), which could signal long-term difficulties with EF.…”
Section: Ef In Postinstitutionalized Childrenmentioning
confidence: 99%
“…Children are institutionalized due to different factors like abandonment, orphaning, maltreatment and also physical or mental disabilities. Many authors have related the institutionalization with a lack of stimulation in different spheres like motor, cognitive and social-affective [2][3][4], since factors like the absence of personalized treatment according to the ratio between infants and caregivers (15:1) [5] and the lack of quality care of caregivers [6,7] since the poor commitment for wellbeing of infants and the poor response and insensibility for the necessities of the infants [8], the round-toclock type of work [1], the constant rotation of caregiver [9] and the lack of professional training of caregivers [8] among others deficiencies. Therefore, institutionalization has been associated with consequences in brain and behavioral development.…”
Section: Institutionalizationmentioning
confidence: 99%